Assessing The Fulfillment Of The Rights Of Non-Civil Servant Government Employees In Bawaslu Boalemo Regency - Dewi Anggraini Yustika Putri Olii (Universitas Negeri Gorontalo, 2019)
This research aims to find out and analyze How the Implementation of Article 88 Paragraph (1) of Law No. 13 of 2003 on the Fulfillment of The Rights of Non-Civil Servants in Bawaslu Boalemo Regency and What Factors Hinder the Fulfillment of The Rights of Non-Civil Servant Government Employees in Bawaslu Boalemo Regency. The research adopted by researchers is an empirical law researcher with a sociological juridical research model. using the type of approachPerundang-invitation and the case approach. In addition, the research conducted by researchers will be descriptive. Based on the results of research and discussion resulted in conclusions. Fulfillment of the Rights of Non-Civil Servant Government Employees (PPNPNPN) in Bawaslu Boalemo Regency has not been able to be adjusted with UMP Gorontalo Province this is because the Wages paid by the government to PPNPNPN employees are adjusted to the SBM (Input Fee Standard) that has been set by Bawaslu RI even in Perbawaslu who regulates the basics of maximizing salaries by the local UMP Regional. In the payment of PPNPN income, the Work Unit must pay attention to the ceiling in dipa which is the highest limit in disbursing PPNPN income funds. Disbursement of funds must not exceed the DIPA ceiling limit. Second, factors that hinder the fulfillment of the rights of non-civil servants (PPNPN) in Bawaslu Boalemo regency are (1) Bawaslu Boalemo regency is not a PPNPN institution; (2) Bawaslu Boalemo Regency Has Not Become an Independent Working Unit; (3) There has been no Adjustment of Wage Related Budget by the Planning and Budgeting Section.Keywords: Fulfillment of Rights; Employment Agreement; Wages/ Salaries; PPNPN Employees.